OFC/NFOEC 2007 - 2007 Conference on Optical Fiber Communication and the National Fiber Optic Engineers Conference 2007
DOI: 10.1109/ofc.2007.4348673
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed and High-Power Performance of a Dual-Step Evanescently-Coupled Uni-Traveling-Carrier Photodiode at a 1.55¿m Wavelength

Abstract: We demonstrate a dual-step evanescently-coupled uni-traveling-carrier photodiode to minimize the dependence of responsivity on cleaved-length. High responsivity (0.9A/W), wide electrical bandwidth (~60GHz), and high saturation current-bandwidth product (>780mA-GHz) have been achieved simultaneously under 50Ω load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…For example submicron lithography is often required to fabricate the laterally tapered couplers [7]. Recently it has been shown that the critical taper technology can be replaced by exploiting mode-beating effects in coupled multimode waveguides [13][14][15][16][17]. Figure 3 shows a schematic of an evanescently coupled photodiode that utilizes a short multimode input waveguide with optical matching layers [14].…”
Section: A Optical Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example submicron lithography is often required to fabricate the laterally tapered couplers [7]. Recently it has been shown that the critical taper technology can be replaced by exploiting mode-beating effects in coupled multimode waveguides [13][14][15][16][17]. Figure 3 shows a schematic of an evanescently coupled photodiode that utilizes a short multimode input waveguide with optical matching layers [14].…”
Section: A Optical Couplingmentioning
confidence: 99%
“…However, since the waveguide to photodiode coupling is based on mode interference effects, the coupling efficiency depends on the length of the input waveguide section. This design constraint has been eliminated by using a dual-step coupling region [15,17]. Wu et al have reported high responsivity (~ 0.9 A/W) with a 50 μm tolerance in the length of the input waveguide and bandwidth of 60 GHz [17].…”
Section: A Optical Couplingmentioning
confidence: 99%
“…1(a) and (b) show a conceptual cross-sectional view and top-view of the demonstrated module. Details of the structure of the optical waveguide can be referred to in our previous work [7]. The topmost active absorption region has a typical UTC-PD structure [3] with a 200-nm-thick InP collector.…”
mentioning
confidence: 99%
“…In order to realize the monolithic integration, we adopted the structure of an evanescently coupled photodiode (ECPD) [5] to construct the passive demultiplexer region and active photodiodes. The new ECPD was dual-stage in structure [6], [7] and different from that discussed in previously research [5]. It was difficult to fabricate due to the long ( 700 m) and tapered optical waveguide utilized for the power coupling process.…”
mentioning
confidence: 99%
See 1 more Smart Citation